Psychometric Assessment of the Persian Version of the Structured Multidisciplinary Work Evaluation Tool (SMET) Questionnaire among Nurses - MasoumehAlsadat Mousavi kani; Zeinab Kazemi; Marzieh Izadi Laybidi; Ehsan Garosi; Jamileh Abolghasemi; Mohammad Sadegh Ghasemi (بهداشت و ایمنی کار)
Introduction: Nurses play a crucial role in hospital settings, often undertaking demanding tasks that exceed their physical and cognitive capacities. The Structured Multidisciplinary Work Evaluation Tool (SMET) is an instrument for evaluating and identifying risks in workplace environments. The objective of this study was to assess the psychometric properties of the Persian (Farsi) version of the SMET. Material and Methods: In this cross-sectional study, the face and content validity of the questionnaire were evaluated both qualitatively and quantitatively by a panel of 13 experts. Quantitative content validity was performed using the Content Validity Ratio (CVR) and Content Validity Index (CVI). Reliability was measured using Cronbach’s alpha and Intraclass Correlation Coefficient (ICC). Results: The face validity assessment revealed that questions 3, 4, 6, 23, and 24 required clarification. The CVI for all items was calculated to be above 0.79. However, several questions had a CVR below 0.54, indicating that specialists considered some questions unnecessary or repetitive. Consequently, these questions were either removed or merged with similar items based on the scores and subsequent reviews. Cronbach’s alpha and ICC values for the entire questionnaire and its dimensions were above 0.7, indicating acceptable to strong reliability. Conclusion: The Persian version of the SMET questionnaire demonstrated acceptable psychometric properties for comprehensive multifactorial evaluation of healthcare workplaces.